THE ESTABLISHMENT OF THE KHWAREZMSHAH STATE DURING THE ANUSHTEGENIAN HORSELESS PERIOD - Qilichev Shohruh Sheraliyevich (Western European Studies, 2025)
This article discusses the period of the rise to power of Atsiz, the ruler of the Anushtegid dynasty, and his campaigns with Sultan Sanjar
Keywords: Anushtegin; Sultan Malikshah; Malik Abu Muzaffar Alovuddin Jalaluddin Atsiz